122P Local thermal ablation reboots the response in advanced hepatocellular carcinoma with stable or atypical progressive diseases during anti-PD-1 therapy. (15th December 2019) - Zhao, M; Huang, J; Lyu, N; Kong, Y; Mu, L; Lin, Y
Abstract: Background: The anti-programmed cell death protein-1 (PD-1) inhibitor is the recommended second-line therapy for advanced hepatocellular carcinoma (HCC) after sorafenib failure. However, only a small subset of patients benefited from anti-PD-1 therapy due to a limited response rate. The goal of this study is to evaluate the impact of ablation on the tumor in patients with advanced HCC who had stable disease or atypical response during single anti-PD-1 therapy after sorafenib failure. Methods: This prospective study enrolled 50 patients treated with an anti-PD-1 inhibitor of nivolumab or pembrolizumab monotherapy between July 2015 and Nov 2017. Thirty-three cases with stable disease or atypical response to anti-PD-1 inhibitor received subtotal thermal ablation. The safety and the response of ablation during anti-PD-1 therapy were evaluated. The survival was estimated by the Kaplan-Meier curve. Results: Of all 50 patients treated with anti-PD-1 therapy, the rate of response, stable disease, atypical and typical progression were 10% (n = 5), 42% (n = 21) 32% (n = 16) and 12% (n = 6), respectively. Additional ablation improved efficacy with tolerable toxicity, and the response rate was increased from 10% to 24% (12/50). The median time to progression, progression-free survival, and overall survival were 6.1 months (95% confidence interval [CI], 2.6-11.2), 5 months (95%CI, 2.9-7.1) and 16.9 months (95%CI, 7.7-26.1), respectively. Conclusion: Additional ablation could increase the objective response rate with tolerated toxicity and achieved a relatively better median survival, in advanced HCC patients who had stable or atypical progressive diseases during anti-PD-1 therapy, which may provide a potentially promising strategy to treat advanced HCC. Clinical trial identification: NCT03939975. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.